Examining within- and across-day relationships between transient and chronic stress and parent food-related parenting practices in a racially/ethnically diverse and immigrant population - Jerica M. Berge; Allan Tate; Amanda Trofholz; Angela Fertig; Scott Crow; Dianne Neumark-Sztainer; Michael Miner (BMC, 2018)
Abstract Background Although prior research suggests that stress may play a role in parent's use of food-related parenting practices, it is unclear whether certain types of stress (e.g., transient, chronic) result in different food-related parenting practices. Identifying whether and how transient (i.e., momentary; parent/child conflict) and chronic (i.e., long-term; unemployment >6 months) sources of stress are related to parent food-related parenting practices is important with regard to childhood obesity. This is particularly important within racially/ethnically diverse parents who may be more likely to experience both types of stress and who have higher levels of obesity and related health problems. The current study examined the association between transient and chronic stressors and food-related parenting practices in a racially/ethnically diverse and immigrant sample. Methods The current study is a cross-sectional, mixed-methods study using ecological momentary assessment (EMA). Parents (mean age = 35; 95% mothers) of children ages 5-7 years old (n = 61) from six racial/ethnic groups (African American, American Indian, Hispanic, Hmong, Somali, White) participated in this ten-day in-home observation with families. Results Transient stressors, specifically interpersonal conflicts, had significant within-day effects on engaging in more unhealthful food-related parenting practices the same evening with across-day effects weakening by day three. In contrast, financial transient stressors had stronger across-day effects. Chronic stressors, including stressful life events were not consistently associated with more unhealthful food-related parenting practices. Conclusions Transient sources of stress were significantly associated with food-related parenting practices in racially/ethnically diverse and immigrant households. Chronic stressors were not consistently associated with food-related parenting practices. Future research and interventions may want to assess for transient sources of stress in parents and target these momentary factors in order to promote healthful food-related parenting practices.